TINJAUAN YURIDIS ASAS KEPERCAYAAN TERHADAP JUAL BELI DI KANTIN KEJUJURAN UNIVERSITAS ISLAM MALANG PERSPEKTIF KUH PERDATA DAN HUKUM ISLAM - bayu pratama (Dinamika, 2022)
ABSTRACKBuying and selling transactions at the honesty canteen are buyers taking the purchased goods, putting their own money at the place of payment, and if there is change, the buyer takes the change himself at the place of payment. With the presence of the transaction model, it is interesting to do research with the formulation of the problem, namely, first,How is buying and selling in the honesty canteen of the Islamic University of Malang based on the perspective of the Civil Code and Islamic law? Second, how is the application of the principle of trust to buying and selling in the honesty canteen of the Islamic University of Malang? The type of research used in this research is empirical legal research (empirical juridical) and sociological juridical approach. The sale and purchase agreement carried out in the honesty canteen is essentially in the essential element of this sale and purchase agreement. If the buyer does not pay the purchase price, the seller can demand the cancellation of the purchase, in accordance with the provisions of Articles 1266 and 1267 of the Civil Code. Then the buying and selling carried out in the honesty canteen has met the requirements, where the seller is mature and has sense.Keywords: Cheese Canteen, Basic Beliefs, Civil Code, Islamic LawABSTRAKTransaksi jual beli di kantin kejujuran adalah para pembeli mengambil barang pembelian, meletakkan uang sendiri ditempat pembayaran, dan jika ada kembalian, maka pembeli mengambil sendiri kembaliannya ditempat pembayaran tersebut, Dengan hadirnya model transaksi tersebut, maka menarik untuk dilakukan penelitian dengan rumusan masalah yaitu, pertama, Bagaimana jual beli di kantin kejujuran Universitas Islam Malang berdasarkan perspektif KUH Perdata dan hukum islam? Kedua, Bagaimana penerapan asas kepercayaan terhadap jual beli di kantin kejujuran Universitas Islam Malang? Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian hukum empiris (yuridis empiris) dan pendekatan yuridis sosiologis. Perjanjian jual beli yang dilakukan di kantin kejujuran intinya berada pada unsur esensialia sebuah perjanjian jual beli ini, Jika si pembeli tidak membayar harga pembelian, si penjual dapat menuntut pembatalan pembelian, sesuai dengan ketentuan Pasal 1266 dan 1267 KUHPerdata. Kemudian jual beli yang dilakukan di kantin kejujuran ini sudah memenuhi syarat, dimana penjual sudah baligh dan berakal.Kata Kunci: Kantin Kejujuraan, Asas Kepercayaan, KUHPerdata, Hukum Islam